Peningkatan Hasil Belajar Siswa Kelas X IPS 2 SMA 1 Wabula dengan Menggunakan Model Problem Based Learning pada Materi Litosfer dan Dampaknya Terhadap Kehidupan - Haryati Haryati; Sitti Kasmiati; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
The learning outcomes of class X IPS 2 students at Senior High School 1 Wabula on the Lithosphere material remain low due to one-way teaching that provides little room for student engagement. This condition reflects the low quality of the geography learning process that needs to be improved. This study aims to describe student learning activities, describe teacher teaching activities, and determine the improvement of student learning outcomes in class X IPS 2 Senior High School 1 Wabula taught using the Problem Based Learning model on the Lithosphere and Its Impact on Life material. The results of the study show an increase in student learning activities from the